2022
DOI: 10.1101/2022.02.08.479118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in interactions over ecological time scales influence single cell growth dynamics in a metabolically coupled marine microbial community

Abstract: Microbial communities thrive in almost all habitats on earth. Within these communities, cells interact through the release and uptake of metabolites. These interactions can have synergistic or antagonistic effects on individual community members. The collective metabolic activity of microbial communities leads to changes in their local environment. As the environment changes over time, the nature of the interactions between cells can change. We currently lack understanding of how such dynamic feedbacks affect … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…To study this, we used degrader-cross-feeder co-cultures involving Neptunomonas and Alteromonas strains. The individual interactions between Neptunomonas and V. splendidus and Alteromonas and V. natriegens strains have previously been studied in detail (28, 29). These studies revealed that both the Alteromonas and Neptunomonas strain were cross-feeders in the sense that they are unable to degrade chitin or consume primary degradation products such as mono- or dimers and instead rely on metabolic by-products excreted by the degraders, such as acetate for carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…To study this, we used degrader-cross-feeder co-cultures involving Neptunomonas and Alteromonas strains. The individual interactions between Neptunomonas and V. splendidus and Alteromonas and V. natriegens strains have previously been studied in detail (28, 29). These studies revealed that both the Alteromonas and Neptunomonas strain were cross-feeders in the sense that they are unable to degrade chitin or consume primary degradation products such as mono- or dimers and instead rely on metabolic by-products excreted by the degraders, such as acetate for carbon sources.…”
Section: Resultsmentioning
confidence: 99%